Numerical and laboratory investigation of fatigue prediction models of asphalt containing glass wastes - Mohammad Taghipoor (14152497) (2020)
In the present study, the finite element method was applied to model the fatigue behavior of glassphalt and conventional mixtures. In order to assess the efficiency level of the presented model, all mixtures were tested using 4-point bending test. Accordingly, it can be seen that there is high consistency between the laboratory results and outputs of 3D finite element model presented in this study in both conventional asphalt and glassphalt mixes. The estimation models have predicted the fatigue life of similar samples with only a 3% error. Also, laboratory results showed a 5% improvement in the fatigue performance of the glassphalt rather than conventional mixtures. Other Information Published in: International Journal of Fatigue License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijfatigue.2020.105819